Desenvolvimento de resinas novolac a partir do líquido da casca da castanha de caju como agente de cura para resina epóxi - Silva, Kássia Teixeira da (2021)
Phenolic resins are the most widely used thermoset polymers in the world today, used in different industrial segments, with great prominence in the field of adhesives. However, the compounds used in conventional production are considered highly toxic and carcinogenic. In order to promote na alternative and sustainable process for obtaining these materials, this work aimed to develop phenolic resins from CNSL, a by- product of agribusiness, a natural source of phenols and suitable to be used as raw material in the synthesis of phenolic resins. The synthesis was performed using paraformaldehyde and oxalic acid as a catalyst, without addition of solvente. Its viscosity was evaluated every 60 minutes, totaling 5 hours of reaction time. The reaction conditions resulted in resins of high molar mass, thermally stable, with different structural and viscosity features. The curing reaction of the novolac resin was proposed by combining with a commercial epoxy resin, bisphenol A diglycidyl ether (DGEBA), in different concentrations, using 1-butylimidazole as a catalyst, eliminating the use of conventional hardeners. The use of epoxy-phenol system proved to be efficient and promising in obtaining new highly cross-linked polymers with excellent thermal properties. The application of the epoxy-phenol system as an adhesive for wood was evaluated through the shear strength test. It was observed that the physical properties of the adhesives were, in fact, influenced by the increase in the degree of crosslinking of the polymer. The results showed the potential use of the combination of novolac resins synthesized from the CNSL and DGEBA epoxy resin in the field of adhesives.